Nivel de conocimiento sobre la evaluación formativa en docentes de nivel primaria de instituciones educativas pertenecientes a la Unidad de Gestión Educativa Local 02 - Nolazco Galloso, Juan Cesar (2020)
The objective of this research was to determine the level of knowledge on the formative assessment that teachers have at the primary level of the educational institutions that belong to the Unidad de Gestión Educativa Local 02 according to their initial training and years of service. For this, the research was of a quantitative type, of descriptive level, of non-experimental design and cross-section. The study subjects are 30 primary school teachers who work in educational institutions located in the districts of Independencia, Los Olivos, Rímac and San Martin de Porres. The instrument Cuestionario sobre el nivel de conocimiento de la evaluación formativa was applied, validated by Rosales (2018), and descriptive statistics were used to analyze the data. The results found that teachers at the primary level of educational institutions that belong to the Unidad de Gestión Educativa Local 02 have a medium level of knowledge about formative assessment.